A Longitudinal Study of Corporate Social Disclosures in a Developing Economy - Mahadeo, J. D.; Oogarah-Hanuman, V.; Soobaroyen, T. (2011)
This article examines corporate social disclosures (CSD) in an African developing economy (Mauritius) as provided in the annual reports of listed companies from 2004 to 2007. Informed by the country’s social, political and economic context and legitimacy theory, we hypothesise that the extent and variety of CSD themes (social, ethics, environment and health and safety) will be enhanced post-2004 and will be influenced by profitability, size, leverage and industry affiliation. We find a significant increase in the volume and variety of CSD, although information in relation to social activities remains the most prominent form of disclosure. This is in contrast to previous studies which reported on the primacy of employee disclosures in developing countries. Using a pooled regression analysis, we also observe that size does explain variations in overall CSD and social disclosures, whilst leverage is positively related to changes in environmental and health and safety disclosures. There is no profitability relationship, and the effects of industry affiliation on CSD are non-significant or contrary to expectations. Overall, we assert that legitimacy, as a strategic and managerially driven approach favouring symbolic actions, is the prevailing motivation underlying the progression of CSD in Mauritius.
Keywords: annual reports; Mauritius; Legitimacy theory; Developing economy; Corporate social disclosures